Strategi Pemberdayaan UMKM di Kabupaten Agam - Mansur, Yuwarman (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This study describes the Strategy for Empowering Micro, Small, and Medium Enterprises (MSMEs) conducted by the Agam Regency Government through the Office of Cooperatives, Micro and Small and Medium Enterprises, Industry, and Trade. This is motivated by the existence of empowerment programs included in two patterns, namely the pattern of empowering development and empowerment patterns of assistance in efforts to enable MSMEs in Agam Regency. Researchers then compare what happens to business actors. Providing capital assistance, training, mentoring activities, and product promotion significantly empowers MSMEs in Agam Regency. In addition, the empowerment program carried out by the Agam Regency Government through the Office of Cooperatives, Micro and Small and Medium Enterprises, Industry, and Trade is in the form of the establishment of a business-owned business entity, providing a business gallery of business production, launching E-UMKM applications, formation of forums MSMEs, establish business partnerships and market expansion. The research method used is descriptive qualitative, providing an objective picture or explanation related to the empowerment of MSMEs by the Agam Regency Government. The results of this study indicate that the empowerment of MSMEs in Agam Regency in the form of programs included in the pattern of guidance and assistance has been effective and beneficial for business actors.